2022
DOI: 10.1097/md.0000000000030286
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of dance therapy using telerehabilitation on trunk control and balance training in patients with stroke: A pilot study

Abstract: Background: This randomized controlled trial aimed to investigate the effects of dance therapy using telerehabilitation on trunk control and balance training in patients with stroke and compare them with the effects of conventional treatment. Methods: We enrolled 17 patients with subacute or chronic stroke who were randomly assigned to either an experimental or a control group. In addition to conventional physical therapy, the experimental group (n = 9) participated in 40-minute, non-face-to-face, dance-ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…A total of 315 unique records were initially retrieved in our literature search, leaving 282 records after removing duplicates, which were reduced to 56 records after title and abstract screening. After careful full-text screening, nine RCTs (328 patients) ( 9 , 30 33 , 49 52 ) were identified to comply with the request of our systematic review and were included in the meta-analysis. Each study was published in English between 1 January 2020 and 31 December 2022.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 315 unique records were initially retrieved in our literature search, leaving 282 records after removing duplicates, which were reduced to 56 records after title and abstract screening. After careful full-text screening, nine RCTs (328 patients) ( 9 , 30 33 , 49 52 ) were identified to comply with the request of our systematic review and were included in the meta-analysis. Each study was published in English between 1 January 2020 and 31 December 2022.…”
Section: Resultsmentioning
confidence: 99%
“…One study ( 49 ) indicated that it was difficult to blind caregivers, therapists, and patients due to the nature of the intervention. Two studies ( 9 , 31 ) did not report blinding, while the remaining studies reported well-developed blinding. Most studies had fewer data on incomplete outcomes, except for two studies ( 31 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations